Estudo de caso sobre a gestão documental e preservação das coleções fonográficas da Rádio Cultura de Belém do Pará - SOUZA, Priscila Lins (2017)
This research studies the document management and preservation of record collections in Radio Cultura at Belém do Pará, using as the archivistic perspective. With the advancement on information technology, there have been changes in the media of phonographic documents, creating a phenomena that affects document management and should be discussed in Archivology. The aim is to examine the record collection of Radio Cultura to make a description of its document management and conservation routines within the particularities of a hybrid collection of materials, ie, analog and digital.